Time management: An imperative for schools - James-Reid, Olga H. (My University, 1992)
This paper reports on a preliminary study on time management in 22 primary and all-age schools in Jamaica. Data were collected from observation of teachers at work in seven classrooms, and from a questionnaire administered to teachers from 15 schools. Results of the analysis showed, among other findings, that school time is not adequately used by teachers with instructional time being seriously affected by non-instructional time or activities.
Biennial Cross-Campus Conference on Education, 2nd, St. Augustine, Trinidad, 22-24 April, 1992